Morbidity and Function Loss After Resection of Malignant Peripheral Nerve Sheath Tumors. Issue 3 (March 2022) - Martin, Enrico; Pendleton, Courtney; Verhoef, Cornelis; Spinner, Robert J.; Coert, J. Henk
Abstract : BACKGROUND: Malignant peripheral nerve sheath tumors (MPNSTs) are aggressive soft tissue sarcomas. Their resection may lead to serious morbidity. Incidence of postoperative motor and sensory deficits is unknown, and reconstruction aimed at restoring such deficits is infrequently carried out. OBJECTIVE: To identify the incidence and risk factors of postoperative morbidity in MPNST as well as the use and outcomes of functional reconstructions in these patients. METHODS: Postoperative function and treatment of MPNSTs diagnosed from 1988 to 2019 in 10 cancer centers was obtained. Two models were constructed evaluating factors independently associated with postoperative motor (<M3) or critical sensory loss. Critical sensation was defined as partial or complete loss of hand, foot, or buttocks sensation. RESULTS: A total of 756 patients (33.4% neurofibromatosis type 1, NF1) were included. MPNSTs originated in 34.4% from a major nerve. Of 658 surgically treated patients, 27.2% had <M3 muscle power and 24.3% critical sensory loss. Amputations were carried out in 61 patients. Independent risk factors for motor and sensory loss included patients with NF1, symptomatic, deep-seated, extremity, or plexus tumors originating from major nerves (all P < .05). A total of 26 patients underwent functional reconstructions. The majority (64%) of these patients regained at least M3 muscle power and 33% M4 despite 86% receiving multimodal therapy. CONCLUSION: Resection of MPNSTs commonly results in motor and sensory deficits. Patients with NF1, symptomatic, deep-seated tumors, arising from major nerves were associated with a higher risk for developing postoperative morbidity. Functional reconstructions are infrequently performed but can improve functional outcomes.